2021
DOI: 10.3390/jcm10215085
|View full text |Cite
|
Sign up to set email alerts
|

Blood Neurofilament Light Chain in Parkinson’s Disease: Comparability between Parkinson’s Progression Markers Initiative (PPMI) and Asian Cohorts

Abstract: Elevated blood neurofilament light chain (NfL), which indicates the loss of neuronal integrity, is increasingly implicated as a diagnostic and outcome-predicting biomarker for neurological diseases. However, its diagnostic implication for Parkinson’s disease (PD) remains unclear, with conflicting data reported by several studies. This may result from the demographic heterogeneity of the studied cohorts. The present study investigated the comparability of blood NfL between a domestic, single-centered PD cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…1c). The lower concentration of NfL in PD compared to HC samples was in agreement with a recent paper by Chen et al who reported similar ndings in an Asian cohort (10). Moreover, Chen et al reported that the lower in NfL plasma concentration was statistically signi cant only in females.…”
supporting
confidence: 91%
“…1c). The lower concentration of NfL in PD compared to HC samples was in agreement with a recent paper by Chen et al who reported similar ndings in an Asian cohort (10). Moreover, Chen et al reported that the lower in NfL plasma concentration was statistically signi cant only in females.…”
supporting
confidence: 91%
“…NfL is a well-recognised disease non-specific marker of neuroaxonal damage, and its role as marker of neurodegeneration has been established in AD 21,[28][29][30] . In PD, however, there is not enough evidence to support its use as early diagnostic biomarker 22 and, similarly to our findings, some studies have failed to demonstrate a difference in plasma NfL among PD and HC 31,32 , despite its utility in discriminating PD from APD 24,30 . Nevertheless, both CSF and plasma NfL concentrations have been associated with a more severe neurodegenerative process 21,24,31,33 , similarly to what is found in APD or in PD with additional cognitive impairment, which in turn reflects a more widespread Lewy body pathology 4 .…”
Section: Discussionsupporting
confidence: 56%
“…1c), even after the data were adjusted for age. The lower concentration of NfL in PD compared to HC samples was in agreement with a recent paper by Chen et al [9] who found that the difference was statistically significant only in females. Consistently, in our cohort, we found lower NfL concentrations in both PD and MSA samples from females but not from males (Additional file 1: Fig.…”
supporting
confidence: 93%